Phthalate esters in surface sediments from fishing ports in Circum-Bohai-Sea region, China. (October 2021) - Liu, Binxu; Jiang, Tao; Li, Zhiying; Ge, Wei; Wu, Juan; Song, Ningning; Chai, Chao
Abstract: The concentration, composition, distribution, and possible sources of phthalate esters (PAEs) in surface sediments from fishing ports in the Circum-Bohai-Sea region were investigated. The potential ecological risks of PAEs on three sensitive aquatic organisms (algae, crustacean, and fish) were assessed based on the risk quotient. The concentrations of 16 PAEs were in the range of 8.53–86.13 μg/g. Six PAEs, which were considered as priority pollutants by the United States Environmental Protection Agency, were main congeners. Fishing ports with high PAE concentration were located near the eastern area of the Shandong Peninsula, the southern area of the Liaodong Peninsula, and the estuary of the Yellow River. Wastewater, atmospheric deposition, plastic, and rubber products were possible sources of PAEs. The PAEs showed medium to high ecological risks on the three aquatic organisms, and the ecological risks were attributed to four PAEs, including dimethyl phthalate, diethyl phthalate, dibutyl phthalate, and benzylbutyl phthalate. Highlights: The levels of PAE in fishing ports in Circum-Bohai-Sea region were medium to high. The positive result of PAEs was in the range of 92.5%–100% in fishing ports. DEHP and DEP were important congeners discriminating PAE pollution. Possible sources were wastewater, atmospheric deposition, plastic, and rubber. Risks were attributed to DMP, DEP, DBP, and BBP with medium to high levels.